Electron paramagnetic resonance of the primary radical pair [D-center dot+Phi(A)(center dot-)] in reaction centers of photosynthetic bacteria - Proskuryakov, I; Klenina, I; Hore, P; Bosch, M; Gast, P; Hoff, A (1996)
Using continuous wave EPR spectroscopy with a high time resolution, a new short-lived signal at g=2 is observed in bacterial photosynthetic reaction centers in which electron transfer past the bacteriopheophytin ΦA is blocked. This signal decays with a time constant equal to the rise time of the triplet state of the primary donor 3D, and is therefore attributed to the primary radical pair [D·+ Φ·-A]. Applying the theory of spin-correlated radical pairs, the spectrum could be satisfactorily simulated, yielding the following magnetic interaction parameters between D·+ and Φ·-A: exchange interaction JDΦ = -0.9 ± 0.1 mT and JDΦ = -1.7 ± 0.1 mT for reaction centers of Rhodobacter sphaeroides R26 and Rhodopseudomonas viridis, respectively, and an axial dipolar interaction DDΦ = -3.0 ± 0.5 mT for Rhodopseudomonas viridis. The implications of the magnitude and sign of the exchange parameters for the energetics of photosynthetic electron transfer are discussed.